(untitled) (Vietnam Journal of Community Medicine, 2021)
There are 11 rooms and 38 departments with 1791 staffs in Thu Duc District Hospital. Moreover, there are above 6000 patients coming for examination and approximately over 900 in-patients at the hospital. Although the medical solid waste management was concentrated and focused on, there is still some insufficient points that need to be researched. Therefore, we are now proceeding in researching our aim to describe the reality of medical solid waste management at Thu Duc District Hospital in 2019 and evaluate the factor that affects the waste management. The method for this research is cross-section descriptive research. We have observed all tools, equipments used for managing medical solid waste, and observed the medical solid waste classification in 36 departments/ clinical units, paraclinical, also have used designed inventory. The result is shown that ratio of accurate sorting of medical solid waste was still low, only 65.1%. Therein, the lowest ratio is in accurate sorting of medical solid waste without recycle, 69.8 %. Next, the ratio of correct sorting of recycled medical solid waste is 71.7 % and the ratio of correct sorting of dangerous uninfected medical solid waste is 75.4%.